Pengaruh Lingkungan Kerja, Semangat Kerja, Kompensasi, dan Loyalitas Terhadap Kinerja Driver Gojek di Kota Pontianak - Kuswiyanto, Putra Adi; Firayanti, Yuni; Marhamah, Marhamah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the influence of work environment, work enthusiasm, compensation, and loyalty on the performance of Gojek drivers in Pontianak City. The phenomenon of declining performance and loyalty among some drivers, along with unstable income and uncertain incentives, serves as a critical background for this study. Driver performance, as the frontline of Gojek's services, is influenced by both internal and external factors, such as the quality of the work environment, individual work enthusiasm, the compensation system, and loyalty to the company. The research method uses a quantitative approach with data collection techniques through the distribution of questionnaires to 96 active Gojek drivers in Pontianak City. The data were analyzed using multiple linear regression tests with the SPSS 20 program. The results of the study indicate that, simultaneously, work environment, work enthusiasm, compensation, and loyalty have a positive effect on performance, with an F-value of 64.687 and a significance level of 0.000 < 0.05. Partially, the work environment (X1) had a negative effect with a value of -13.440, work enthusiasm (X2) had a positive effect with a value of 3.117, compensation (X3) had a positive effect with a value of 2.489, and loyalty (X4) had a positive effect with a value of 9.535. The regression equation is Y = 11.936 - 0.415 + 0.155 + 0.135 + 0.405, with an R² value of 0.740. These findings indicate that improvements in driver performance are more strongly influenced by work enthusiasm, compensation, and loyalty than by the work environment.